Tinjauan Literatur: Pemanfaatan Tes Intelegensi dalam Layanan Bimbingan dan Konseling untuk Mengoptimalkan Perkembangan Akademik Peserta Didik - Khusnul Neva; Elsa Julianti; Melta Aprillia Santi; Syawallina Khoirunisa; Minarsi Minarsi; Yola Eka Putri (Lembaga Pengembangan Kinerja Dosen, 2026)
This study is motivated by the suboptimal use of intelligence tests in guidance and counseling services in schools, despite their important role in understanding students’ cognitive abilities as a basis for providing appropriate services. This study aims to examine the utilization of intelligence tests in guidance and counseling services to support the optimization of students’ academic development. The method used is a literature review with a qualitative approach through the analysis of 25 relevant scientific articles published between 2022 and 2026, using content analysis techniques. The results indicate that intelligence tests play an important role in identifying cognitive abilities, supporting the planning of guidance and counseling services, assisting in academic decision-making, and guiding interventions for students’ learning difficulties. In addition, intelligence is also related to academic achievement, although it is influenced by other factors such as motivation and the learning environment. However, the findings also reveal a gap between the theoretical potential of intelligence test utilization and its implementation in practice, which still faces limitations, particularly in the integration of assessment results and the accuracy of interpretation. The implications of this study highlight the need to improve counselors’ competence in the use of psychological assessments and to optimize the systematic use of test results in order to support more effective guidance and counseling services in developing students’ academic potential.